Microarray analysis reveals that dietary retinoic acid suppresses cancer-related gene expression of the lungs of cigarette smoke-exposed rats - Xue, Yuan; Meadors, Edward P.; Wang, Weiqun; Baybutt, Richard C. (My University, 2012)
Previously we found that cigarette smoke depleted vitamin A in the lungs and induced tracheal precancerous lesions. To understand the molecular consequences underlying cigarette smoke-induced vitamin A depletion and its associated lung cancer risk, this study investigated the lung cancer-related genes in cigarette smoke-exposed rats with or without dietary retinoic acid, the active metabolite of vitamin A. Twenty-four male weanling rats were fed either a control or a retinoic acid supplemented diet. Half of each group was exposed to 40 commercial cigarettes/ d, 5 d/ wk. After 4 weeks, the rats were sacrificed and their lungs were immediately frozen. Total RNA was extracted and purified, from which cDNA was synthesized and labeled for gene expression analysis. Expressions of 120 genes were measured via a customized microarray. In lungs exposed to cigarette smoke, most of the genes involved in cell division, transcription and cell adhesion were up-regulated. The dietary retinoic acid treatment of the cigarette smoke-exposed lungs was found to down-regulate most of the genes involved in similar functions. In addition, retinoic acid down-regulated four genes, Egr1, Fos, Icam1 and Mmp9, all of which were up-regulated by cigarette smoke. These findings suggest possible molecular mechanisms of cigarette smoke induced-lung cancer and define potential targets of retinoic acid anticarcinogenic actions.
Keywords: Cancer; Smoking; Retinoic acid; Cigarette; Genomics